MEMBONGKAR NU MAGELANG (Menakar ke"NU"an warga Nahdhiyin Magelang antara NU Kultural dan Struktural dan Pengaruhnya Terhadap Pemberdayaan Masyarakat) - Moh Fatkhan (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2015)
Magelang is one of territorial base of NU in Central Java, as a santri territory it has very strong  tradition  of pesantren. The pesantren tradition deep-rooted in NU, has a princip  that the kiai is a figure cannot be opposed by its santris or its followers. The strong pesantren tradition in the NU's affiliate influences the way ofNU's organization in many levels whether it is in regency level (cabang), district level (anak cabang), and village level (ranting). The ideal ofNU's organization not only exists and operates in the level of regency (cabang) and district (anak cabang) but also should exist and operate in every villages (ranting). However in reality, NU at Magelang regency in structural/jamiah/organizational level is very alarming. This is proven by the very few ofNU's organization in the level of village/ranting that exist and operate. Some ofMagelang residents are more proud to declare theirself  as cultural NU than structural NU. Many NU's affiliates do not want to be verified as a member of NU's organization, having Kartanu (NU member  card), moreover became NU's officer, though culturally they are NU's  affiliate. This condition besides has an effect  in NU's organization also has consequence in political reality in Magelang regency, such as the defeat  in legislative  election  and Magelang regent election. Therefore by carry out field research, researcher will try to describe objective condition the respons ofNU's affiliate in Magelang regency towards NU's organization Magelang regency from the perspective of cultural NU's community as the target object and their influence to the empowerment of Magelang community.